Kekurangan Energi Kronis Pada Ibu Hamil Trimester I Berdasarkan Usia Dan Graviditas - Kusniyati Utami; Irni Setyawati; Dian Soekmawaty Riezqy Ariendha (Poltekkes Kemenkes Kupang, 2020)
Introduction: Chronic energy deficiency (CED) is one of the non-obstetric medical complications in pregnancy that can be enforced by examining the upper arm circumference of less than 23.5 cm in pregnant women. Pregnant women who experience CED can cause stunted fetal growth which results in low birth weight babies. The prevalence of CED in pregnant women in West Nusa Tenggara Province (NTB) is higher than the prevalence of Indonesia which is equal to 21.5% (Indonesia: 17.3%). The purpose of this study was to determine the incidence of CED in pregnant women based on age and gravidity. Methodology: This study was an observational analytic study with cross sectional approach. Population of this research was all pregnant women in five hamlets in the Poskesdes Sesela 2 with a total sample of 137 people using total population sampling techniques. This research was conducted in the Poskesdes Sesela 2 working area of ​​the UPT BLUD Puskesmas Gunungsari, West Lombok in November 2019 until January 2020. The data source was secondary that was analyzed univariately and bivariately using the Chi-Square test. Result & Discussion: The result shows tha the majority pregnant women in Poskesdes Sesela 2 in 2019 are aged 20-35 years which is 79.1. Most parity of pregnant woman is multigravida at 62.2%. Most of the pregnant women who did not experience CED that is equal to 79.7%. There is a significant difference in the incidence of CED of pregnant women aged <20 years and those aged 20-35 years (p-value 0.03). There was a significant difference in the incidence of CED between primigravida and multigravida pregnant women (p-value 0,0004). Health workers, especially midwives in villages or primary healthcare, are expected to be able to measure LILA in young women or prospective brides as an early detection of CED events before pregnancy so that proper management can be done before pregnancy occurs and can reduce the morbidity and mortality rates of mothers and fetuses during pregnancy and childbirth.